Building a well-balanced culture in the perioperative setting. Issue 2 (August 2022) - Bello, Corina; Filipovic, Mark G.; Andereggen, Lukas; Heidegger, Thomas; Urman, Richard D.; Luedi, Markus M.
Abstract : Healthcare institutions are currently under enormous financial, political and social pressure. Especially in the perioperative setting, various professional groups with differing agendas, dynamic teams, high-stress levels and diverging stakeholder interests are contributing to tension on a variety of levels. These players ask for guidance that goes beyond defined goals, clear structures or rules for process optimization. The impact of culture, which is influenced by core values, unspoken behaviours and practices, a shared purpose and implicit norms, has been often neglected. However, culture is a key factor in the search for optimal patient outcomes, quality of care, protection and long-time retention of staff, as well as economic success. In this review, we discuss important aspects to consider in building a great perioperative workplace, discuss indispensable adaptations in times of crisis and touch on urgently needed further investigations to optimize the art of developing, protecting, and cultivating a well-balanced culture.